Análise de perfis de comprometimento organizacional e sua relação com o desempenho humano: uma abordagem psicossocial - Barbosa, Daniel Araújo (2019)
Organizational commitment has been presented in the literature as a category among the psychological linkages between workers and organizations, being the three-dimensional model of Meyer and Allen (1991) the most widely used in the construct approach. The evolution of the studies has indicated work performance as a consequent, associated more strongly to affective and normative bases of commitment. However, the category of human performance at work has been primarily addressed as an objective variable, sometimes represented only by its results and not in a behavioral perspective. This study aimed to investigate the relationships between organizational commitment profiles and human performance, being the latter approached from the psychosocial point of view, through a model of four constitutional behavioral factors. Specifically, it sought to identify the possible relationships between organizational commitment profiles, their constituent factors (or bases), and the self-reported human performance in their constituent factors, as well as to highlight the possible differences between these relationships. This was a quantitative study, descriptive and explanatory, applied to a sample of 249 workers from the universe of two companies located in Fortaleza/CE, operating in the industrial and logistic segment. Data were collected through a survey and the collection instrument consisted of a structured questionnaire, composed of two scales that identified the investigated constructs. Data analysis was done through descriptive statistics (measures of central tendency, frequency distribution and dispersion), Pearson correlation analysis and cluster analysis. The study identified four clusters of profiles of commitment and positive correlations between normative base and tasks execution and evaluation in both organizations, and between affective and normative bases and self-management of performance in the industrial organization. There were negative correlations between the affective basis of the different profiles and the performance restriction factor among the participants in the industry. No significant correlations were identified between the commitment bases and strategic alignment of performance.